Impact of Financial Literacy on Investment Decisions of Retail Investors in the Nepalese Stock Market: A Structural Equation Modeling Approach (OCEM Journal of Management, Technology & Social Sciences, 2024)
The structure refers to the component of the building that maintains its financial literacy is crucial for influencing an individual’s financial behaviors, particularly concerning investment choices. The central objective of this study was to assess the impact of financial literacy dimensions on the investment decisions of retail investors in the Nepalese stock market. The current study applied a causal-comparative research design. The convenience sampling technique was used to select samples, and a total of four hundred twenty nine samples were collected from retail investors of the Nepal Stock Exchange using a structured survey questionnaire. The data was analyzed using IBM SPSS 26 and AMOS 22. The study employed a diverse array of statistical methods for data assessment, including reliability analysis, descriptive statistics, correlation analysis, exploratory factor analysis, confirmatory factor analysis, and structural equation modeling (SEM). SEM path analysis was applied to test the hypotheses. The study suggests that financial knowledge, financial behavior, and financial skills significantly impact retail investors’ investment decisions. Thus, the findings indicated that retail investors who possess greater financial knowledge, exhibit positive financial behaviors, and have strong financial skills are more inclined to make well-informed and advantageous investment choices. However, the findings also indicate that financial attitude does not influence the investment decisions of retail investors. This study could potentially contribute to the academic discourse on behavioral finance and financial literacy, offering empirical evidence tailored to the Nepalese context. Future research can broaden their scope by examining additional variables such as personality traits, emotional intelligence, behaviuoral biases, and relationships among them in the Nepalese stock market.